(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The investigation of Farabi on «the virtuous city” is related with the justice, equality, society, peace, and happiness becomes as an actual matter, in connection with the processes of globalization of the world, it also deals with the foundation of the unity of the world community. This article considers an essence of philosophy of the morale of al-Farabi and its influence on the further development of the ethic thought.